Radionuclides measured on 37 water bottle profiles during POLARSTERN cruise ARK-XXII/2 - Pinghe Cai; Michiel M Rutgers van der Loeff; Ingrid Stimac; Eva-Maria Nöthig; Kate Lepore; S Bradley Moran (PANGAEA, 2010)
The loss of Arctic sea ice has accelerated in recent years. With the decline in sea ice cover, the Arctic Ocean biogeochemistry is undergoing unprecedented change. A key question about the changing Arctic Ocean biogeochemistry is concerning the impact of the shrinking sea ice cover on the particulate organic carbon (POC) export from the upper Arctic Ocean. Thus far, there are still very few direct measurements of POC export in the permanently ice-covered central Arctic Ocean. A further issue is that the magnitude of the POC export so far documented in this region remains controversial. During the ARK-XXII/2 expedition to the Arctic Ocean from 28 July to 7 October in 2007, we conducted a high-resolution study of POC export using 234Th/238U disequilibrium. Depth profiles of total 234Th in the upper 200 m were collected at 36 stations in the central Arctic Ocean and its adjacent seas, i.e., the Barents Sea, the Kara Sea and the Laptev Sea. Samples were processed using a small-volume MnO2 coprecipitation method with addition of a yield tracer, which resulted in one of the most precise 234Th data sets ever collected. Thorium-234 deficit with respect to 238U was found to be evident throughout the upper 100 m over the Arctic shelves. In comparison, 234Th deficit was confined to the upper 25 m in the central Arctic Ocean. Below 25 m, secular equilibrium was approached between 234Th and 238U. The observed 234Th deficit was generally associated with enhanced total chlorophyll concentrations, indicating that in situ production and export of biogenic particles are the main mechanism for 234Th removal in the Arctic Ocean. Thorium-234-derived POC fluxes were determined with a steady state model and pump-normalized POC/234Th ratios on total suspended particles collected at 100 m. Results showed enhanced POC export over the Arctic shelves. On average, POC export fluxes over the various Arctic shelves were 2.7 ± 1.7 mmol m**-2 d**-1 (the Barents Sea), 0.5 ± 0.8 mmol m**-2 d**-1 (the Kara Sea), and 2.9 ± 1.8 mmol m**-2 d**-1 (the Laptev Sea) respectively. In comparison, the central Arctic Ocean was characterized by the lowest POC export flux ever reported, 0.2 ± 1.0 mmol m**-2 d**-1 (1 standard deviation, n = 26). This value is very low compared to prior estimates and is also much lower than the POC export fluxes reported in other oligotrophic oceans. A ThE ratio (234Th-derived POC export/primary production) of <6% in the central Arctic Ocean was estimated using the historical measurements of primary production. The low ThE ratio indicates that like other oligotrophic regimes, the central Arctic Ocean is characterized by low POC export relative to primary production, i.e., a tightly coupled food web. Our study strongly suggests that the current role of the central Arctic Ocean in C sequestration is still very limited. Meanwhile, this role might be altered because of global warming and future decline in sea ice cover.
Supplement to: Cai, P et al. (2010): Low export flux of particulate organic carbon in the central Arctic Ocean as revealed by 234Th:238U disequilibrium. Journal of Geophysical Research: Oceans, 115, C10037, https://doi.org/10.1029/2009JC005595